2019
DOI: 10.33314/jnhrc.v16i41.1607
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Behavioral Problems among Adolescents in Pokhara City in Nepal

Abstract: Background: Adolescents are highly vulnerable to psychiatric disorders, which often have serious negative consequences for their academic achievement and potential social life. The aim of the study is to estimate the prevalence of emotional and behavioral problems among adolescents.Methods: A descriptive cross-sectional study design was adopted to identify the emotional and behavioral problems among adolescents using cluster sampling technique. Assessment was done on students of grade 7-11 from two schools in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Most studies link externalizing behavior to gender [128]. Hitherto, boys lead girls in any given methodology such as self, teacher scores and parental scores [121]. The present study has extended gender differentials in externalizing behavior disorders to different age groups, school type, and school level.…”
Section: Externalizing Behavior Is Associated With Gendermentioning
confidence: 76%
See 1 more Smart Citation
“…Most studies link externalizing behavior to gender [128]. Hitherto, boys lead girls in any given methodology such as self, teacher scores and parental scores [121]. The present study has extended gender differentials in externalizing behavior disorders to different age groups, school type, and school level.…”
Section: Externalizing Behavior Is Associated With Gendermentioning
confidence: 76%
“…Furthermore, the association confers different behavioral patterns in privately owned and publicly funded primary and secondary schools. Although, it has been shown by [121] that students in secondary schools have twice more odds to exhibit externalizing behavior than their colleagues in private schools, this present study considered both primary and secondary schools. The outcome is highly expected because of the income disparity in Nigeria.…”
Section: Externalizing Behavior Is Associated With School Typementioning
confidence: 99%
“…Em uma pesquisa comparativa com adolescentes do Nepal, por meio do YSR, verificou-se que PI (35,8%) também foram mais comuns que PE (18,5%) m uma amostra de 330 adolescentes (Sharma et al, 2019), com resultados semelhantes ao aqui encontrados.…”
Section: Discussionunclassified
“…18 Other studies in Nepal state that 12.9-30% of adolescents had psychosocial problems. 5,19,20 In our findings anxiety disorders were found to be the commonest, this is similar to the meta-analysis done by Polanczyk,et al 6.5%, 21 on the worldwide prevalence of mental disorders in children and adolescents, similar findings were recorded by Pillai, et al 1%, 10 Roberts 6.9%, 22 Mishra 15%, 23 Kessler, et al 24 In a study done in Dang district, (46.5%) of the secondary school adolescents had anxiety. 25 Our study showed mood disorder to be the second most common disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients diagnosed with a psychiatric disorder were in the age group years 17-19 yrs 109 (60.28%) with a male preponderance 56 (51.77%). Male to female ratio 1.07:1 and the majority of them were single 165 (95.04%).…”
mentioning
confidence: 99%